Electroacupuncture may protect pulmonary dysplasia in offspring with perinatal nicotine exposure by altering maternal gut microbiota and metabolites - Xie, Yana; Fang, Yang; Liu, Yitian; Ji, Bo; Sakurai, Reiko; Wang, Yifei; Li, Hewen; Zhang, Ling; Wu, Le; Guo, Tingting; Quan, Ye; Rehan, Virender K. (Frontiers in Microbiology, 2025)
BackgroundPerinatal nicotine exposure (PNE) induces pulmonary dysplasia in offspring and it increases the risk of respiratory diseases both in offspring and across generations. The maternal gut microbiota and its metabolites, such as short-chain fatty acids (SCFAs), can regulate fetal lung development and are susceptible to nicotine exposure. Therefore, modulation of PNE-induced changes in maternal gut microbiota and SCFAs may prevent the occurrence of pulmonary dysplasia in offspring.ObjectiveOur previous studies demonstrated that electroacupuncture (EA) ameliorated PNE-induced impairment in offspring lung development. To further our study, we aimed to determine whether the protective effect of EA is associated with the modulation of changes in maternal gut microbiota and SCFAs.MethodsWe observed changes in maternal gut microbiota and serum SCFA levels in both mother and offspring after EA treatment using a PNE rat model. Furthermore, using broad-spectrum antibiotics, we established a pseudo-germ-free PNE rat model to explore whether EA can protect offspring’s pulmonary function and lung morphology in the presence of depleted maternal gut microbiota.ResultsOur study revealed that EA increased the community richness (Sobs index) of perinatal nicotine-exposed maternal gut microbiota and the abundance of beneficial bacteria (RF39, Clostridia, Oscillospirales, etc.). This was accompanied by an upregulated serum levels of acetate, butyrate, and total SCFAs in both mother and offspring rats, as well as stimulated expression of SCFA receptors (GPR41 and GPR43) in the lung tissue of offspring rats. However, the beneficial effects of EA on offspring pulmonary function (FVC, PEF, PIF, and Cdyn) and lung morphology (alveolar number and MLI) were lost after maternal gut microbiota depletion.ConclusionThese findings suggest that EA may exert its therapeutic effects on PNE-induced lung phenotype by altering maternal gut microbiota. The likely mechanism involves the associated improvement in serum SCFA levels in both mother and offspring, as well as the upregulation of SCFA receptors in the lung tissue of offspring.